A new species of Coenosopsia Malloch (Diptera, Anthomyiidae) from southern Brazil and a reappraisal of the cladistic relationships of the genus - Bortolanza, Mariza; de Carvalho, Claudio J. B.; Lara, Ana P. C. (Zootaxa, 2006)
A new species of Coenosopsia Malloch (Diptera, Muscidae), C. albuquerquei Bortolanza and Carvalho, sp. nov., is described from Telêmeco Borba, in the state of Paraná, southern Brazil. With this new species included, a cladistic re-analysis of the genus was performed, using the data matrix of Nihei and Carvalho (2004). Results of this analysis suggest a close relationship between C. albuquerquei and C. ferrari. This clade is the sister-group of the other Coenosopsia species: (C. prima (C. brasiliensis, C. peruviana) (C. michelseni (C. floridensis, C. mexicana))). Biogeographically, the vicariant events previously proposed for South America support the evolutionary history of this genus. Additionally, we discuss the possibility that C. michelseni and C. ferrari were not always restricted to the “cerrado” of central Brazil.